KONSEP NORMATIF SANKSI PIDANA TERHADAP PELAKU PERUNDUNGAN (BULLYING) UNTUK MEWUJUDKAN KEPASTIAN HUKUM - Haryanto, Rudi; Kristiawanto, Kristiawanto; Basuki, Basuki (SINERGI : Jurnal Riset Ilmiah, 2025)
Bullying is a deliberate, repeated, and systematic behavior aimed at causing physical or psychological discomfort to others, often carried out for the perpetrator’s own amusement in witnessing the victim’s suffering. Bullying can take the form of mocking, insulting, making offensive remarks, or spreading false stories that isolate the victim or make them the subject of ridicule, leading to feelings of inferiority, fear, and distress. This behavior is increasingly concerning, as it affects various groups ranging from children to adults and can result in severe physical and psychological consequences, including fatal actions such as suicide. This study aims to analyze the effectiveness of criminal law in addressing bullying in Indonesia and to explore future normative concepts of criminal sanctions that combine both repressive and restorative approaches. The research problems raised in this study are. the current concept of criminal sanctions against bullying perpetrators, and the normative concept of criminal sanctions needed to ensure legal certainty in the future. Theories used in this research include the theory of punishment and the theory of legal certainty. he research method used is a normative legal approach. This study uses a statute approach, a case approach and a comparative approach which in principle originates from primary legal materials consisting of laws and judges' decisions, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The legal material analysis technique uses grammatical interpretation techniques. This study reveals that the current concept of criminal punishment for bullying perpetrators in Indonesia adopts a mixed theory that combines retribution, prevention, and rehabilitation. However, the legal framework remains fragmented and unsystematic, leading to legal uncertainty and inconsistent law enforcement. To ensure legal certainty and public protection, a specific and comprehensive regulation on bullying is needed, including both criminal sanctions and additional penalties such as account suspension, content removal, temporary social media bans, public apologies, restitution, community service, and revocation of certain rights. The study also recommends the establishment of anti-bullying response units in educational institutions and workplaces, integrated with law enforcement and relevant agencies, to provide early detection, reporting mechanisms, and appropriate follow-up for bullying cases